Cool thermodynamics : The engineering and physics of predictive, diagnostic and optimization methods for cooling systems - Gordon, Jeffrey M.; Ng, Kim Choon (New Delhi : Viva Book, 2015)
This book is geared toward those interested in the engineering and physics of air-conditioning and refrigeration devices (chillers). Analytic thermodynamic models are developed for a wide variety of cooling systems and a broad range of operating conditions. These models are easily implemented in the field or laboratory. Although we focus upon mechanical (electrically-driven) chillers - primarily reciprocating and centrifugal machines - there is also substantial material on heat-driven absorption chillers. Heat pumps and heat transformers are also addressed. A few less common chiller types are also treated, such as thermoelectric, thermoacoustic and vortex-tube units. We have tried to present the material in a manner that can appeal to both the engineer and the physicist, and can form a bridge between the two communities in their analysis and presentation of cooling systems. In each chapter, we try to capture the basic physics of the problem, and to emerge with quantitatively accurate predictive and diagnostic tools.
Includes References and index
Keywords: Thermodynamics; Heat engineering; Cooling systems; Energy conversion; Air conditioning